Water : Vital for Life - Kocienda, Genevieve (NewYork Cambridge University, 2014)
Water is one of the most essential ingredients for life on Earth. This reader looks at water in all its forms - in the air, on the ground, in the oceans, in our pipes - and explains how water keeps our lives moving.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: Pre-Intermediate Level; English language